Asia leading power as a Global Logistics force - Nicolas Hernandez Bertel (World Scientific Reports, 2024)
In recent decades, Asia has emerged and has firmly established itself as a dominant force as a Global Logistics force, taking the lead as a player in the international logistics landscape due to its gigantic economic growth, vast manufacturing capacity and substantial investments in Top-notch infrastructure, and major industrialization adopt with progressive policies that attract foreign investment in logistics. By its strategic location, this continent occupies a central position in global trade routes, acting as a bridge between key markets in America, Europe and the Middle East. This advantageous location enables the movement of goods worth billions of dollars each year with rapid industrialization and rising consumer demand, taking center stage as a destination of choice for shippers and manufacturers seeking to strengthen and diversify their supply chains. Driving unprecedented and progressive changes, the continent’s integration into the world economy has revolutionized the global trade dynamics and perspective of other regions. The world’s second most integrated trade region, China, Japan, Singapore and India are the Outstanding countries in that region to be now categorized as a logistics powerhouse facilitating international trade reshaping global supply chains focusing on the keys of leading on the distribution, transport and infrastructure contributes with a significant portion of nearly 40% of the world's total exports and imports.